2010
DOI: 10.1145/1670671.1670673
|View full text |Cite
|
Sign up to set email alerts
|

Cognitive transfer of spatial awareness states from immersive virtual environments to reality

Abstract: Accuracy of memory performance per se is an imperfect reflection of the cognitive activity (awareness states) that underlies performance in memory tasks. The aim of this research is to investigate the effect of varied visual fidelity on the transfer of training to the real-world after exposure to immersive simulations representing a real-world scene. A between groups experiment was therefore carried out to explore the effect of rendering quality on measurements of location-based recognition memory for objects … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
3
3
2

Relationship

1
7

Authors

Journals

citations
Cited by 40 publications
(13 citation statements)
references
References 23 publications
0
12
0
1
Order By: Relevance
“…In addition, the level of confidence for each answer from the participants were also tested in this paper because the memory score in 'confidence in brand preference' needs the high level of confidence for correct answers [7]. Result showed that if the participants liked the picture given to him, the participants will remember the objects in the panoramic view [9]. Besides that, if the participants gave the correct answer, the level of confidence on participant also will be high.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the level of confidence for each answer from the participants were also tested in this paper because the memory score in 'confidence in brand preference' needs the high level of confidence for correct answers [7]. Result showed that if the participants liked the picture given to him, the participants will remember the objects in the panoramic view [9]. Besides that, if the participants gave the correct answer, the level of confidence on participant also will be high.…”
Section: Discussionmentioning
confidence: 99%
“…Marks will be given based on correct answers only. Recognition Memory is a memory test involving a person's ability to identify the weaknesses in the picture [7] [9]. Participants will be given a picture that there are some errors.…”
Section: Memory and Memory Testmentioning
confidence: 99%
See 1 more Smart Citation
“…In VR, Mania et al [9] and Stinson et al [16] recently looked at the effects of visual realism on training transfer. Mania investigated the effect of different shading techniques (flat-shading or radiosity) on a memory task.…”
Section: Related Workmentioning
confidence: 99%
“…Subject-oriented experiments currently planned at the Technical University of Crete aim to measure how lighting manipulations and varied rendering quality affect the normal population's spatial awareness while navigating a 3D scene comprising of a lounge and an external yard (Fig. 2) as well as feelings of presence, subjective responses to lighting and performance when performing formal spatial cognition and spatial memory tasks [3], [4].…”
Section: Experiments 2: Exploring the Effect Of Lightingmentioning
confidence: 99%